PEMBERIAN SANKSI SEBAGAI UPAYA PENERTIBAN PENCATATAN PERKAWINAN DI INDONESIA - Adi Syahputra Sirait (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This paper aims to analyze and explain how the Labuhanbatu law enforcers view the discourse of imposing sanctions for those who do not register marriages through government regulation number 9 of 1975 concerning the implementation of law number 1 of 1974 concerning marriages whose implementation is not effective, the method used in writing This is a descriptive qualitative approach to the law, the source of the data in this paper was obtained through interviews with law enforcers in Labuhanbatu. Labuhanbatu law enforcers are of the view that the order for registration of marriages contained in law number 1 of 1974 must be accompanied by sanctions, either in the form of imprisonment or fines, as in other Islamic countries so as to regulate the administration of marriage registration in Indonesia, because of its impact. can harm husbands, wives and children in a family, such as rights, obligations and other interests.